2006
DOI: 10.1590/s0100-204x2006000600021
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização parcial e utilização da fitase extraída de sementes germinadas de girassol

Abstract: Resumo -O objetivo deste trabalho foi ativar, extrair e caracterizar parcialmente a fitase em sementes germinadas de girassol (Helianthus annuus L.), híbrido M734, e avaliar o efeito da fitase no farelo de girassol. Sementes foram colocadas para germinar por oito dias em câmara a 25°C. A fitase foi extraída com CaCl 2 2%, depois do quinto dia de germinação, e fracionada com (NH 4 ) 2 SO 4 até 80% de saturação. O extrato bruto foi caracterizado parcialmente e aplicado em farelo de girassol desengordurado para a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…(CHENG;HARDY, 2002). Studying phytase derived from sunflower seeds, Agostini and Ida (2006) verified no loss of phytase activity within a temperature range between 30 to 50 o C. In another study, comparing some sources of the phytase of stemmed cereals, Esmaeilipour et al (2012) observed that the enzyme stability becomes impaired at temperatures above 80 °C, which is close to the extrusion temperature used in this trial.…”
mentioning
confidence: 57%
“…(CHENG;HARDY, 2002). Studying phytase derived from sunflower seeds, Agostini and Ida (2006) verified no loss of phytase activity within a temperature range between 30 to 50 o C. In another study, comparing some sources of the phytase of stemmed cereals, Esmaeilipour et al (2012) observed that the enzyme stability becomes impaired at temperatures above 80 °C, which is close to the extrusion temperature used in this trial.…”
mentioning
confidence: 57%
“…Hybrid sunflower M734 phytase is heatstable at 50°C for 10 min. When added to deffated sunflower flour after 8h of incubation, it hydrolyzed 92% of phytate (Agostini and Ida, 2006b). Thus, the objective of this work was to investigate the reduction of the PA content in two hybrid sunflowers by enhancing the phytase and acid phosphatase activities during natural germination.…”
Section: Introductionmentioning
confidence: 99%